The barley amo1 locus is tightly linked to the starch synthase IIIa gene and negatively regulates expression of granule-bound starch synthetic genes - Li, Zhongyi; Li, Dehong; Du, Xihua; Wang, Hong; Larroque, Oscar; Jenkins, Colin L. D.; Jobling, Stephen A.; Morell, Matthew K. (Journal of experimental botany, 2011)
In this study of barley starch synthesis, the interaction between mutations at the sex6 locus and the amo1 locus has been characterized. Four barley genotypes, the wild type, sex6, amo1, and the amo1sex6 double mutant, were generated by backcrossing the sex6 mutation present in Himalaya292 into the amo1 'high amylose Glacier'. The wild type, amo1, and sex6 genotypes gave starch phenotypes consistent with previous studies. However, the amo1sex6 double mutant yielded an unexpected phenotype, a significant increase in starch content relative to the sex6 phenotype. Amylose content (as a percentage of starch) was not increased above the level observed for the sex6 mutation alone; however, on a per seed basis, grain from lines containing the amo1 mutation (amo1 mutants and amo1sex6 double mutants) synthesize significantly more amylose than the wild-type lines and sex6 mutants. The level of granule-bound starch synthase I (GBSSI) protein in starch granules is increased in lines containing the amo1 mutation (amo1 and amo1sex6). In the amo1 genotype, starch synthase I (SSI), SSIIa, starch branching enzyme IIa (SBEIIa), and SBEIIb also markedly increased in the starch granules. Genetic mapping studies indicate that the ssIIIa gene is tightly linked to the amo1 locus, and the SSIIIa protein from the amo1 mutant has a leucine to arginine residue substitution in a conserved domain. Zymogram analysis indicates that the amo1 phenotype is not a consequence of total loss of enzymatic activity although it remains possible that the amo1 phenotype is underpinned by a more subtle change. It is therefore proposed that amo1 may be a negative regulator of other genes of starch synthesis.